A method to solve separable fuzzy nonlinear programming problem. (2017) - Chakraborty, Debjani; Singh, Vishnu Pratap
This paper formulates piecewise fuzzy linear approximation of fuzzy nonlinear function of a single variable. First, we construct the equation of fuzzy line segment through two fuzzy points using -cuts of two fuzzy points. Now the fuzzy nonlinear function is represented by a set of connected fuzzy line segments. Fuzzy line segments have been defined by partitioning the domain of a fuzzy nonlinear function. Then formulation of approximating fuzzy linear programming problem has been given to find the solution of fuzzy nonlinear separable programming problem. An illustrative example is given to demonstrate the methodology.